ANALISIS HOMA TERHADAP RESISTENSI INSULIN DAN FUNGSISEL β PANKREAS PADA TIKUS WISTAR (Rattus norvegicus) MODEL DIABETES ALOKSAN SETELAH PEMBERIAN EKSTRAK BONGGOLNANAS (Ananas comosus (L.) Merr.) - Muhammad Azka Azkiya Arif; Yosha Putri Wahyuni; Isniani Ramadhani; Cut Fauziah (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Diabetes mellitus refers to a metabolic condition characterized by resistance to insulin and abnormalities in pancreatic β-cell function. Pineapple core (Ananas comosus (L.) Merr.) is known to contain bioactive compounds with potential effects on glucose also insulin metabolism. This research aimed to analyze insulin sensitivity using HOMA-IR also HOMA-β in alloxan-induced diabetic Wistar rats (Rattus norvegicus) following administration of pineapple core (Ananas comosus (L.) Merr.) extract. This study employed an experimental laboratory design with a posttest-only control group. Male Wistar rats were induced with alloxan and divided into a control groups and treatment groups receiving graded doses of pineapple core (Ananas comosus (L.) Merr.) extract. Fasting blood glucose levels were measured using a glucometer, while plasma insulin levels were determined using the ELISA method. HOMA-IR and HOMA-β values were calculated to asses insulin sensitivity also pancreatic β- cell function. The results showed a significant difference in HOMA-IR and HOMA- β values between the negative control group and the high dose treatment group (100%) (treatment 3), with a p-value of 0.034. Pineapple core (Ananas comosus (L.) Merr.) extract has the potential to enhance pancreatic β-cell function and significantly improve insulin resistance based on HOMA-IR also HOMA-β parameters in alloxan-induced diabetic Wistar rats.